Discordance Between SARS-CoV-2–specific Cell-mediated and Antibody Responses Elicited by mRNA-1273 Vaccine in Kidney and Liver Transplant Recipients. Issue 12 (17th November 2021) - Fernández-Ruiz, Mario; Almendro-Vázquez, Patricia; Carretero, Octavio; Ruiz-Merlo, Tamara; Laguna-Goya, Rocío; San Juan, Rafael; López-Medrano, Francisco; García-Ríos, Estéfani; Más, Vicente; Moreno-Batenero, Miguel; Loinaz, Carmelo; Andrés, Amado; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Severe acute respiratory syndrome coronavirus 2–specific cell-mediated immunity (SARS-CoV-2-CMI) elicited by mRNA-based vaccines in solid organ transplant (SOT) recipients and its correlation with antibody responses remain poorly characterized. Methods: We included 44 (28 kidney, 14 liver, and 2 double organ) recipients who received the full series of the mRNA-1273 vaccine. SARS-CoV-2-CMI was evaluated at baseline, before the second dose, and at 2 wk after completion of vaccination by an ELISpot-based interferon-γ FluoroSpot assay using overlapping peptides covering the S1 domain. SARS-CoV-2 immunoglobulin G seroconversion and serum neutralizing activity against the spike protein were assessed at the same points by commercial ELISA and an angiotensin-converting enzyme-2/spike antibody inhibition method, respectively. Postvaccination SARS-CoV-2-CMI was compared with 28 healthcare workers who received the BNT162b2 vaccine. Results: Positive SARS-CoV-2-CMI increased from 6.8% at baseline to 23.3% after the first mRNA-1273 dose and 59.5% after the completion of vaccination ( P < 0.0001). Lower rates were observed for immunoglobulin G seroconversion (2.3%, 18.6%, and 57.1%, respectively) and neutralizing activity (2.3%, 11.6%, and 31.0%). There was a modest correlation between neutralizing titers and the magnitude of SARS-CoV-2-CMI (Spearman's rho: 0.375; P = 0.015). Fifteen recipients (35.7%) mounted SARS-CoV-2-CMI without detectable neutralizing activity, whereas 3 (7.1%) did the opposite, yielding poor categorical agreement (Kappa statistic: 0.201). Rates of positive SARS-CoV-2-CMI among SOT recipients were significantly decreased compared with nontransplant controls (82.1% and 100.0% after the first dose and completion of vaccination, respectively; P < 0.0001). Kidney transplantation, the use of tacrolimus and prednisone, and the number of immunosuppressive agents were associated with lower cell-mediated responses. Results remained unchanged when 3 recipients with prevaccination SARS-CoV-2-CMI were excluded. Conclusions: Two-thirds of SOT recipients mounted SARS-CoV-2-CMI following vaccination with mRNA-1273. Notable discordance was observed between vaccine-induced cell-mediated and neutralizing humoral immunities. Future studies should determine whether these patients with incomplete responses are effectively protected.